The effect of probiotic Escherichia coli strain Nissle 1917 lipopolysaccharide on the 5-aminosalicylic acid transepithelial transport across Caco-2 cell monolayers - Stětinová, Věra; Smetanová, Libuše; Kholová, Dagmar; Květina, Jaroslav; Svoboda, Zbyněk; Zídek, Zdeněk; Tlaskalová-Hogenová, Helena (General physiology and biophysics, 2013)
The object of this study was to investigate the effect of probiotic Escherichia coli strain Nissle 1917 (EcN) (i) EcN lipopolysaccharide (EcN LPS) and (ii) bacteria-free supernatant of EcN suspension (EcN supernatant) on in vitro transepithelial transport of mesalazine (5-aminosalicylic acid, 5-ASA), the most commonly prescribed anti-inflammatory drug in inflammatory bowel disease (IBD). Effect of co-administered EcN LPS (100 µg/ml) or EcN supernatant (50 µg/ml) on the 5-ASA transport (300 µmol/l) was studied using the Caco-2 monolayer (a human colon carcinoma cell line) as a model of human intestinal absorption. Permeability characteristics for absorptive and secretory transport of parent drug and its intracellularly-formed metabolite were determined. The quantification of 5-ASA and its main metabolite N-acetyl-5-amino-salicylic acid (N-Ac-5-ASA) was performed by high performance liquid chromatography. Obtained results suggest that neither EcN LPS nor EcN supernatant had effect on the total 5-ASA transport (secretory flux greater than absorptive flux) and on the transport of intracellularly formed N-Ac-5-ASA (preferentially transported in the secretory direction). The percent cumulative transport of the total 5-ASA alone or in combination with EcN LPS or EcN supernatant did not exceed 1%.
Keywords: Probiotics; biologický transport; antiflogistika nesteroidní; lipopolysacharidy; Escherichia coli; kultivační média speciální; Caco-2 buňky; lidé; Mesalamine; Intracellular Space; Epithelial Cells; Culture Media, Conditioned; Lipopolysaccharides; Biological Transport; Anti-Inflammatory Agents, Non-Steroidal; probiotika; permeabilita; Permeability; intracelulární prostor; mesalamin; Caco-2 Cells; epitelové buňky; Humans